2015
DOI: 10.18632/oncotarget.6574
|View full text |Cite
|
Sign up to set email alerts
|

MKP1 mediates chemosensitizer effects of E1a in response to cisplatin in non-small cell lung carcinoma cells

Abstract: The adenoviral gene E1a is known to enhance the antitumor effect of cisplatin, one of the cornerstones of the current cancer chemotherapy. Here we study the molecular basis of E1a mediated sensitivity to cisplatin in an experimental model of Non-small cell lung cancer. Our data show how E1a blocks the induction of autophagy triggered by cisplatin and promotes the apoptotic response in resistant cells. Interestingly, at the molecular level, we present evidences showing how the phosphatase MKP1 is a major determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In breast cancer, several other studies have indicated that MKP-1 may be an adverse prognostic factor in breast cancer patients and contributes to chemoresistance ( 85 87 88 ). Studies have shown that MKP-1 overexpression lead to increased resistance to cisplatin in human lung cancer cell lines while knockdown of MKP-1 enhanced cisplatin-mediated apoptosis in the lung ( 89 ). Additionally, a recent study reported that MKP-1 translocates to the mitochondria after cell irradiation and inhibits the pro-apoptotic activities of JNK in breast cancer cell lines ( 86 ).…”
Section: Role Of Mkp-1/dusp1 In Cancermentioning
confidence: 99%
“…In breast cancer, several other studies have indicated that MKP-1 may be an adverse prognostic factor in breast cancer patients and contributes to chemoresistance ( 85 87 88 ). Studies have shown that MKP-1 overexpression lead to increased resistance to cisplatin in human lung cancer cell lines while knockdown of MKP-1 enhanced cisplatin-mediated apoptosis in the lung ( 89 ). Additionally, a recent study reported that MKP-1 translocates to the mitochondria after cell irradiation and inhibits the pro-apoptotic activities of JNK in breast cancer cell lines ( 86 ).…”
Section: Role Of Mkp-1/dusp1 In Cancermentioning
confidence: 99%
“…E1A can bind to the proteasomes and inactivate their functions [51,52], preventing the ubiquitin-dependent proteolysis of FoxO3a [23]. E1A also activates PP2A and MKP phosphatases [24,25], which abrogate the degradation of FoxO by reducing its phosphorylation [53,54]. Phosphorylation of FoxO1 by PKB/Akt kinase is an important regulator of FoxO1 activity and stability.…”
Section: Discussionmentioning
confidence: 99%
“…A knockdown of FoxO3a abolished E1A-induced sensitivity to cytotoxic drugs [23]. Moreover, some of the proteins mediating an E1A-induced chemosensitization of tumor cells to apoptosis are either regulators or effectors of FoxOs transcription factors [12,24,25]. One of the molecular mechanisms of E1A-induced chemosensitization is upregulation of protein phosphatases PP2A [24] or MKP1 [25] that are involved in the dephosphorylation and stabilization of FoxOs transcription factors [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E1A expression is also responsible for apoptosis induction in different experimental models, being able to collaborate in chemo and radiotherapy treatments. Recently, we observed that E1A was able to increase cisplatin sensitivity in some resistant NSCLC cell lines (as H1299) through MKP1 transcriptional upregulation mediated by E1A expression [ 4 ]. Indeed, MKP1 knockdown restores chemo resistance in E1A expressing H1299 cell lines, confirming how the axis E1A -> MKP1 -> p38MAPK promotes sensitivity, blocking the characteristic autophagic response associated to resistant models [ 5 ], and promoting an increase in the apoptotic onset.…”
mentioning
confidence: 99%